Uber: natureza jurídica da prestação de serviços pelos motoristas de aplicativo - Fonseca, João José da (2023)
This work addresses, through bibliographical research, the phenomenon of work by application, in order to obtain a solution to the existing debate, especially in the world of law, about the legal nature of the relationship established between digital platforms and service providers who sign up with these new figures. Based on the analysis of the concept of digital platforms and the existing doctrinal and jurisprudential positions regarding the framing of platforms as technology companies or private companies, with a view, primarily, to studying the situation of the Uber platform, together with the examination of the elements that characterize the employment relationship, the legal nature of the contract signed between said company and the drivers linked to it will be discussed, in the light of current Brazilian and foreign jurisprudence